International consensus to standardise histopathological scoring for small bowel strictures in Crohn's disease. Issue 3 (5th May 2021) - Gordon, Ilyssa O; Bettenworth, Dominik; Bokemeyer, Arne; Srivastava, Amitabh; Rosty, Christophe; de Hertogh, Gert; Robert, Marie E; Valasek, Mark A; Mao, Ren; Li, Jiannan; Harpaz, Noam; Borralho, Paula; et al.
Abstract : Objective: Effective medical therapy and validated trial outcomes are lacking for small bowel Crohn's disease (CD) strictures. Histopathology of surgically resected specimens is the gold standard for correlation with imaging techniques. However, no validated histopathological scoring systems are currently available for small bowel stricturing disease. We convened an expert panel to evaluate the appropriateness of histopathology scoring systems and items generated based on panel opinion. Design: Modified RAND/University of California Los Angeles methodology was used to determine the appropriateness of 313 candidate items related to assessment of CD small bowel strictures. Results: In this exercise, diagnosis of naïve and anastomotic strictures required increased bowel wall thickness, decreased luminal diameter or internal circumference, and fibrosis of the submucosa. Specific definitions for stricture features and technical sampling parameters were also identified. Histopathologically, a stricture was defined as increased thickness of all layers of the bowel wall, fibrosis of the submucosa and bowel wall, and muscularisation of the submucosa. Active mucosal inflammatory disease was defined as neutrophilic inflammation in the lamina propria and any crypt or intact surface epithelium, erosion, ulcer and fistula. Chronic mucosal inflammatory disease was defined as crypt architectural distortion and loss, pyloric gland metaplasia, Paneth cell hyperplasia, basal lymphoplasmacytosis, plasmacytosis and fibrosis, or prominent lymphoid aggregates at the mucosa/submucosa interface. None of the scoring systems used to assess CD strictures were considered appropriate for clinical trials. Conclusion: Standardised assessment of gross pathology and histopathology of CD small bowel strictures will improve clinical trial efficiency and aid drug development.